Finite element simulation of transmission and reflection of acoustic waves in the ultrasonic transducer. (1st July 2022) - Shukla, Kaushik; Ahmad, Azeem; Ahluwalia, Balpreet Singh; Melandsø, Frank; Habib, Anowarul
Abstract: In scanning acoustic microscopy (SAM), the image quality depends on several factors such as noise level, resolution, and interaction of the waves with sample boundaries. The theoretical equations for the reflection coefficient and transmission coefficient are suitable for plane boundaries but fail for curved/rough boundaries. We presented a finite element method-based modeling for the loss coefficients in SAM. A focused and unfocused lens with a flat object, furthermore a focused lens with a curved object was selected for loss coefficients calculation. The loss calculation in terms of energy for defining the acoustic reflection and transmission losses and its dependence on the radius of curvature of the test object has also been presented.